Microeconomics - Rubinfeld, Daniel; Pindyck, Robert S. (Boston : Prentice Hall, 2013)
We wrote this book, microeconomics, because we believe that students need to be exposed to the new topics that have come to play a central role in microeconomics over the years.
Introduction : markets and prices -- Producers, consumers, and competitive markets -- Market structure and competitive strategy -- Information, market failure, and the role of government
Includes index.
Keywords: MICROECONOMICS